Phage-dependent changes in Shigella flexneri type antigen synthesis. - Financsek, I (1976)
Lysogenic conversion of Shigella flexneri type antigens was studied with the aid of wild-type and thermosensitive mutant phages. With all wild-type phages, the appearance of glycosylated antigen was accompanied by the appearance of polyprenyl phosphate glucose synthetase activity. With some of the mutant phages, the appearance of glycosylated antigen was not followed by the formation of lipid-linked glucose in the enzyme assay. The reverse has also been observed, i.e., the high rate of formation of lipid-linked glucose and the lack of V-type antigen.